2001
DOI: 10.1097/00000421-200106000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Toremifene in Androgen-Independent Prostate Cancer

Abstract: Toremifene has antiestrogenic and estrogenic properties in vitro and in vivo. In addition, it may have antiangiogenesis and antimicrotubule properties at higher doses. Studies have demonstrated the efficacy of this agent in the treatment of metastatic breast cancer. We performed a phase II trial of toremifene in patients with androgen-independent prostate cancer (AIPC). Patients with an increasing prostate-specific antigen level despite castrate testosterone levels and antiandrogen withdrawal were eligible. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 14 publications
1
21
0
1
Order By: Relevance
“…Thus many estrogens including phytoestrogens, DES and 2-methoxyestradiol as well as selective estrogen receptor modulators (SERMs) including raloxifene, ICI 182,780, trioxifene and torimifene have been shown to affect prostate tumor growth through a variety of mechanisms [20,[120][121][122][123][124][125][126]. While initial clinical trials using tamoxifene and toremifene proved to be unremarkable for the treatment of prostate disease [127,128], more recent Phase II studies indicate that the toremifene may in fact effectively block development and progression of clinical prostate cancer and further clinical trials are underway [126,129]. In is unclear at present whether these agents act primarily through antagonism of ERα or ERβ or whether they differentially modify the actions of both receptors.…”
Section: Estrogen Agonists Antagonists Modulators As Therapeutic Agmentioning
confidence: 99%
“…Thus many estrogens including phytoestrogens, DES and 2-methoxyestradiol as well as selective estrogen receptor modulators (SERMs) including raloxifene, ICI 182,780, trioxifene and torimifene have been shown to affect prostate tumor growth through a variety of mechanisms [20,[120][121][122][123][124][125][126]. While initial clinical trials using tamoxifene and toremifene proved to be unremarkable for the treatment of prostate disease [127,128], more recent Phase II studies indicate that the toremifene may in fact effectively block development and progression of clinical prostate cancer and further clinical trials are underway [126,129]. In is unclear at present whether these agents act primarily through antagonism of ERα or ERβ or whether they differentially modify the actions of both receptors.…”
Section: Estrogen Agonists Antagonists Modulators As Therapeutic Agmentioning
confidence: 99%
“…Earlier studies with experimental models such as R3327 Dunning rat prostate adenocarcinoma [79] and Nb-2Pr-A tumor transplants in Noble rats [80] demonstrated partial growth regression by tamoxifen treatment. The clinical trials with a high-dose treatment with tamoxifen [81] or toremifene [82] were, however, disappointing. Although occasional positive effects were obtained the overall conclusion was that these antiestrogens used in breast cancer treatment did not produce any objective responses in advanced hormone-refractory prostate cancer.…”
Section: Antiestrogen/serm Inhibition Of Progression Of Prostate Cancermentioning
confidence: 99%
“…DES eventually lost favor because of its high cardiovascular toxicity and thromboembolic risk [5], [6], with parenteral estradiol-17β (E2) gaining recent popularity as a therapy for metastatic, castration-resistant PCa (CRPC) [7], [8] because of its low cardiovascular toxicity profile and protective action against osteoporosis [9]. Other selective ER modulators (e.g., tamoxifen, toremifene, and reloxifene) have been investigated in clinical trials but found to have limited efficacy as compared with DES [10]–[13]. With the approval in 2005 of fulvestrant (ICI 182,780), a pure estrogen receptor antagonist with no known agonistic action, for treatment of receptor-positive metastatic breast cancer, interest in its use for CRPC has emerged.…”
Section: Introductionmentioning
confidence: 99%